2017
DOI: 10.1097/npt.0000000000000184
|View full text |Cite
|
Sign up to set email alerts
|

Activity-Based Therapy: From Basic Science to Clinical Application for Recovery After Spinal Cord Injury

Abstract: Background and Purpose Collaboration between scientists and clinicians effectively accelerated translation of scientific evidence for activity-based therapies (ABT) into rehabilitation. This article addresses the basic scientific findings of activity-dependent plasticity that led to Locomotor Training (LT), an ABT, and its principles to advance recovery in adult and pediatric populations with spinal cord injury (SCI). Expansion to new therapies based on these common principles is highlighted, e.g., epidural st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
63
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(64 citation statements)
references
References 35 publications
(61 reference statements)
0
63
0
1
Order By: Relevance
“…Similarly, in animal models of mild or moderate severity incomplete SCI, quadrupedal bodyweight-supported TM training attenuates muscle atrophy, increases muscle force production (Jayaraman, Liu, Ye, Walter, & Vandenborne, 2013;Liu, Bose, Walter, Thompson, & Vandenborne, 2008;Liu et al, 2010;Stevens et al, 2006), and promotes recovery of voluntary over-ground locomotion, in part, by improving afferent neuromodulation of the central pattern generator, by preventing axonal degradation, and by normalizing the spinal reflex pathways that regulate spasticity and motoneuron excitability (Bose, Hou, Parmer, Reier, & Thompson, 2012;Hou et al, 2014). However, after more severe SCI, humans (Behrman, Ardolino, & Harkema, 2017) and animal models (Battistuzzo, Callister, Callister, & Galea, 2012) exhibit only minimal muscular improvement and negligible recovery of over-ground walking ability in response to bodyweight-supported TM training. Similarly, the effectiveness of TM training and of other reloading strategies in regenerating bone after SCI remains contentious (Panisset, Galea, & El-Ansary, 2016), especially at the sites most prone to fracture (i.e., distal femur and proximal tibia) in this population (Cirnigliaro et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in animal models of mild or moderate severity incomplete SCI, quadrupedal bodyweight-supported TM training attenuates muscle atrophy, increases muscle force production (Jayaraman, Liu, Ye, Walter, & Vandenborne, 2013;Liu, Bose, Walter, Thompson, & Vandenborne, 2008;Liu et al, 2010;Stevens et al, 2006), and promotes recovery of voluntary over-ground locomotion, in part, by improving afferent neuromodulation of the central pattern generator, by preventing axonal degradation, and by normalizing the spinal reflex pathways that regulate spasticity and motoneuron excitability (Bose, Hou, Parmer, Reier, & Thompson, 2012;Hou et al, 2014). However, after more severe SCI, humans (Behrman, Ardolino, & Harkema, 2017) and animal models (Battistuzzo, Callister, Callister, & Galea, 2012) exhibit only minimal muscular improvement and negligible recovery of over-ground walking ability in response to bodyweight-supported TM training. Similarly, the effectiveness of TM training and of other reloading strategies in regenerating bone after SCI remains contentious (Panisset, Galea, & El-Ansary, 2016), especially at the sites most prone to fracture (i.e., distal femur and proximal tibia) in this population (Cirnigliaro et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Some of the studies cited involve 100–200 locomotor training sessions. In a recent paper, Behrman recommended at least 60, lasting 1½ h per day for successful Activity Based Therapy ( 7 ). Morrison ( 34 ) provides useful cost data from the US.…”
Section: Discussionmentioning
confidence: 99%
“…Friedli et al (6) found, in 400 patients with tetraplegia, that asymmetry in the lesion allowed greater recovery, and also that, in monkeys, recovery correlated with corticospinal "detour circuits" below the injury. Many animal studies have demonstrated recovery after SCI following treadmill training, and this has reinforced the view that Activity-Based Therapy may enable patients with incomplete lesions to walk (7). Hubli and Dietz (8) described the knowledge gained as a "physiological basis for neurorehabilitation: a sufficient combination of sensory cues is required to generate and improve locomotor patterns.…”
Section: Introductionmentioning
confidence: 99%
“…While these methods are sufficient for the gross evaluation of movement performance and may be easily used in clinical settings, distinctions between intentional movements, unintentional or "reflexive" movements, and "spasms" can be difficult (19). As recovery-focused interventions continue to be developed and improved (21)(22)(23)(24)(25)(26), determination of the presence of residual supraspinal-spinal connectivity after SCI has clear implications for rehabilitation goals and outcomes. There is an important need for age-based assessment of sensorimotor function in children with SCI.…”
Section: Introductionmentioning
confidence: 99%